Prediction of crystallographic cracking planes in single-crystal nickel-base superalloys. (1st June 2018) - Busse, C.; Palmert, F.; Sjödin, B.; Almroth, P.; Gustafsson, D.; Simonsson, K.; Leidermark, D.
Highlights: Development of a crack driving force parameter for crystallographic crack growth. Applicable to 3D models with arbitrary material orientation and crack front shapes. Prediction of crystallographic crack planes after a transition from Mode I cracking. All results have been validated by laboratory tests. Abstract: The inherent anisotropy of single-crystal nickel-base superalloys brings many difficulties in terms of modelling, evaluation and prediction of fatigue crack growth. Two models to predict on which crystallographic plane cracking will occur is presented. The models are based on anisotropic stress intensity factors resolved on crystallographic slip planes calculated in a three-dimensional finite-element context. The developed models have been compared to experiments on two different test specimen geometries. The results show that a correct prediction of the crystallographic cracking plane can be achieved. This knowledge is of great interest for the industry and academia to better understand and predict crack growth in single-crystal materials.